Kajian Kualitatif Peran Stakeholders Dalam Pengembangan Daya Tarik Wisata Kampung Sarugo di Kabupaten Lima Puluh Kota - Aini, Nur; Putra, Trisna (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2024)
The development of tourism in Kampung Sarugo, which is a popular tourist destination, is highly dependent on the participation and support of various stakeholders. The less than optimal role of the contribution of stakeholders to tourism development is the reason for the importance of this research being carried out. The purpose of this study is to identify relevant stakeholders, analyze the uses and roles of stakeholders, analyze the relationships between stakeholders, and inhibiting aspects. The approach used in this research is descriptive qualitative, as well as information gathering methods including interviews, documentation, and observation. The findings show that various groups, including academia, business, community, government, and society, are involved in the creation of tourist attractions. There are three categories of stakeholders: primary, key, and secondary. The role of stakeholders is reflected in the roles of policy creators, coordinators, facilitators, implementers and accelerators.